1987
DOI: 10.1016/0014-5793(87)80448-9
|View full text |Cite
|
Sign up to set email alerts
|

Linear relationships between mitochondrial forces and cytoplasmic flows argue for the organized energy‐coupled nature of cellular metabolism

Abstract: We have studied rates of formation of glucose, urea and lactate by isolated hepatocytes incubated with a variety of inhibitors of energy transduction. Linear relationships have been found between these metabolic rates and mitochondrial forces (membrane, redox and phosphorylation potentials). The findings are suggestive of extensive enzyme organization within these metabolic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Moreover, very little of the resting respiration was responsive to inhibition by oligomycin (6), strongly suggesting that the elevated temperature exacerbated the proton leak of the inner mitochondrial membrane (3). Mitochondrial uncoupling degrades the cytosolic free energy of ATP hydrolysis (G p ) (9), and hepatic gluconeogenic flux has been shown to vary linearly with cellular energy state (2).…”
mentioning
confidence: 99%
“…Moreover, very little of the resting respiration was responsive to inhibition by oligomycin (6), strongly suggesting that the elevated temperature exacerbated the proton leak of the inner mitochondrial membrane (3). Mitochondrial uncoupling degrades the cytosolic free energy of ATP hydrolysis (G p ) (9), and hepatic gluconeogenic flux has been shown to vary linearly with cellular energy state (2).…”
mentioning
confidence: 99%
“…Although this crowded cytosol paradigm has played a major role in the development of major concepts of cell biology, questions have been raised over the years about the validity of this premise (for historical review, see Sols and Marco, 1970;Ottaway and Mowbray, 1977). Extensive research during the last decade has provided even more reason to doubt that view (for selected reviews, see Fulton, 1982;Clegg, 1984;Bhargava, 1985;Welch and Clegg, 1986;Berry et al, 1987;Jones, 1988;Luby-Phelps et al, 1988;Negendank and Edelmann, 1988).…”
mentioning
confidence: 99%
“…There is evidence that alterations in mitochondrial redox may also have significant effects on hepatocyte function and responsiveness. Prior studies with isolated hepatocytes have suggested that the optimal NAD + /NADH for gluconeogenesis and ureagenesis is approximately 1.3 (Berry et al, 1987). Furthermore, the sensitivity of liver to glucagonmediated cytosolic elevations in cAMP and calcium, which increase the activity of key TCA cycle enzymes such as ␣-ketoglutarate dehydrogenase (Rashed and Patel, 1988) and pyruvate dehydrogenase (Walajtys-Rhode et al, 1992), depends on the oxidation-reduction state of liver, whereby extremely low or elevated redox decrease the sensitivity of the response to glucagon (Rashed and Patel, 1987).…”
Section: Discussionmentioning
confidence: 99%